Inhibitory effect of pyrazole derivatives on the P-nitrophenyl phosphate phosphatase activity of alkaline phosphatase - Пенкова, Л.; Павленко, В.; Присяжна, О.; Фрицький, І. (Київський національний університет імені Тараса Шевченка, 2008)
Inhibition efficiency of the catalytic activity of alkaline phosphatase by novel 3,5-substituents of 1H-pyrazolate was examined. This indicates that among four tested compounds there are competitively and uncompetitively inhibitors. It was shown that magnesium ions do not influence on inhibitor effect.

Досліджена ефективність інгібіювання каталітичної активності лужної фосфатази новими 3,5-заміщеними похідними 1H-піразолу. Виявлено, що серед чотирьох досліджуваних сполук є як обернені, так і не обернені інгібітори. Показано, що йони магнію не виявляють впливу на інгібіторний ефект.
Інгібіювання ферментативної активності лужної фосфатази бінуклеативними піразолвмісними лігандами
Keywords: -; -; -